Global Rangelands Data Platform: Development Plan Report - Vizzuality (Vizzuality, 2024)
Presentation of the development plan for the global rangelands data platform being developed by Vizzuality and GMV as a contribution to the GEF-funded IUCN implemented and ILRI exectuted proejct STELARR (Sustainable Investments for Large-Scale Rangeland Restoration).